Develop agent and reseller system in gather deal - Wong, Yong Jie (2024)
The Agent and Reseller System is a web application developed within the Gather Deal framework to simplify commission management processes for resellers and administrators. This project aims to solve the complexities encountered while calculating and managing commissions by providing a centralised system that integrates with Gather Deal's existing infrastructure. The system provides effective commission calculation, sales monitoring, and reporting capabilities through real-time data processing and comprehensive functionality. By using cutting-edge web technologies like Django, React, and Node.js, the system provides resellers with an easy-to-use interface to monitor sales performance, retrieve commissions, and handle their accounts. The system allows administrators to set commission rates, monitor reseller activity, and produce extensive data that may be reviewed further. Ensuring easy adoption and utilisation of the system through comprehensive testing, validation, and documentation improves operational efficiency, decision-making skills, and satisfaction with users across the Gather Deal ecosystem.